ANALISIS SITUASI PEMBANGUNAN MANUSIA JAWA TENGAH DI JAWA TENGAH - Laeli Sugiyono (Department Statistics, Faculty Mathematics and Natural Science, UNIMUS, 2020)
This study aims to analyze the disclosure of the distribution of the position of Regency / City in Central Java based on the Linkage of Economic Growth (EG) and Human Development Index (HDI). The study uses secondary data in the form of cross-sectional regional Regency / City based on EG and HDI Components. Data analysis uses Regency / City distribution plot diagram based on EG and HDI components in the Cartesian diagram which divides the space into 4 quadrants, namely: Awareness I of the City Regency Distribution Plots with high EG and HDI Categories, Quadrant II City Regency Distribution Plots with High HDI Categories, Low EG, Quadrant III HDI Low, High EG, and Quadrant IV Low HDI and EG Categories. This study concludes that the position of Cities in Central Java in general is in line with the Quadrant I group, the HDI of Kota Regency in the area of the ex-Semarang residency and the former residence of Surakarta is in Quadrant I. Whereas other City Regencies are spread in Quadrant II, III, and IV.